Correction to Responding to policy makers’ evaluation needs: combining experimental and quasi-experimental approaches to estimate the impact of performance based financing in Burkina Faso - De Allegri, Manuela; Lohmann, Julia; Souares-Coutant, Aurélia (BMC health services research, 2019)
Due to an error introduced during copyediting of this article [1], there are two corrections about the Figs. 1. The caption of Fig. 1 should be changed to “Study design”. 2. The Fig. 2 is missing.
Gesehen am 03.02.2020